TRANSFORMASI PENDIDIKAN AGAMA ISLAM MELALUI SISTEM PEMBELAJARAN BERBASIS IT: SEBUAH PENDEKATAN FILOSOFIS - ahmad; Asrul (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2024)
The transformation of Islamic religious education through information technology (IT)-based learning systems has a significant impact on the quality of education.This research is motivated by the need to adapt religious education methods and curricula to remain relevant in the digital era.The aim is to analyze the impact of IT usage in Islamic religious education and how a philosophical approach can maintain the balance between technology and religious values.The research method used is a qualitative study with a literature and philosophical approach, which includes the analysis of various sources related to the integration of technology in religious education.The discussion results show that technology enables more flexible and personalized learning, enhancing students' understanding of religious teachings.However, the challenge of maintaining the quality and integrity of digital educational materials requires collaboration between technology experts and religious educators.The conclusion of this research states that the integration of IT in Islamic religious education improves the quality of learning and prepares students to face the challenges of the modern world.The importance of strict oversight mechanisms and continuous training for educators to ensure the wise use of technology and support broader educational goals.Keywords: Transformation of Islamic religious education, information technology, philosophical approach.